2007
DOI: 10.1029/2006ja012225
|View full text |Cite
|
Sign up to set email alerts
|

Continuous quasiperiodic thermospheric waves over Arecibo

Abstract: [1] Incoherent scatter radar (ISR) power profile observations at Arecibo Observatory (AO) have revealed long vertical wavelength (>100 km) quasi-coherent waves with periods of $1 hour that are observed to be nearly continuously present over two $35-hour geomagnetically quiet observation periods. When properly filtered, results from both 22-23 March 2004 and 5-6 June 2005 provide unambiguous views of these waves. The waves are strong throughout the F region, often spanning 160 to above 500 km in altitude and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 51 publications
5
59
0
Order By: Relevance
“…These constraints are less severe for GWs arising at higher altitudes, however, because of the increasing temperatures and scale heights in the thermosphere. Thus we expect that primary sources at much higher altitudes, such as auroral excitation , and references cited above), and secondary sources such as local body forces (Vadas andFritts, 2001, 2002) must also excite GWs at substantially larger spatial scales that can penetrate, in turn, to even higher altitudes, as observed by various authors (Oliver et al, 1997;Djuth et al, 1997Djuth et al, , 2004Livneh et al, 2007). We expect these GWs to have very small initial amplitudes and momentum fluxes, as for the larger scales excited by lower atmosphere sources, but to also experience dramatic amplification factors in propagating to altitudes of 300 km and above.…”
Section: Variations Of Gw Momentum Fluxes and Body Forces With Altitudementioning
confidence: 96%
See 3 more Smart Citations
“…These constraints are less severe for GWs arising at higher altitudes, however, because of the increasing temperatures and scale heights in the thermosphere. Thus we expect that primary sources at much higher altitudes, such as auroral excitation , and references cited above), and secondary sources such as local body forces (Vadas andFritts, 2001, 2002) must also excite GWs at substantially larger spatial scales that can penetrate, in turn, to even higher altitudes, as observed by various authors (Oliver et al, 1997;Djuth et al, 1997Djuth et al, , 2004Livneh et al, 2007). We expect these GWs to have very small initial amplitudes and momentum fluxes, as for the larger scales excited by lower atmosphere sources, but to also experience dramatic amplification factors in propagating to altitudes of 300 km and above.…”
Section: Variations Of Gw Momentum Fluxes and Body Forces With Altitudementioning
confidence: 96%
“…(1) yields the usual inviscid anelastic dispersion relation of Marks and Eckermann (1995). Temperature, density, and wind profiles employed for our study are shown in Fig.…”
Section: Anelastic Viscous Dispersion Relation and Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Djuth et al (2004) suggest that, near Arecibo, there is a continuum of gravity waves in the thermosphere, and that these showed "sets" of waves separated typically by 20-60 min. Livneh et al (2007) used incoherent scatter radar at Arecibo Observatory to observe quasi-coherent continuous waves with periods of ∼1 h in the ionosphere. These are also typical periods of auroral AGWs (Bristow and Greenwald, 1997) that are likely generated by pulsed ionospheric convection (Prikryl et al, 2005) virtually continuously and sometimes observed as TIDs by SuperDARN He et al, 2004).…”
Section: Discussionmentioning
confidence: 99%